Burial history and porosity evolution of Brazilian upper Jurassic to tertiary sandstone reservoirs - Sombra, Cristiano Leite [UNESP]; Chang, Hung Kiang [UNESP] (My University, 1997)
The parameter time-depth index (TDI) is applied in this study to quantify empirically the influence of burial history on sandstone porosity evolution. The TDI, expressed in kilometers per million years of age, is defined as the area in the burial history diagram enclosed by the burial curve of the reservoir and the axes of the diagram. In practice, reservoir depths during burial history are integrated at regular time intervals of 1 m.y. The calculations exclude present-day bathymetry or paleobathymetry. Sandstone reservoirs from several sedimentary basins along the Brazilian continental margin (Santos, Campos, Espírito Santo, Cumuruxatiba, Recôncavo, Sergipe, Alagoas, and Potiguar) were analyzed to investigate the evolution of porosity against TDI. These Upper Jurassic to Tertiary sandstones lie in depths of 700 to 4900 m, and are hydrocarbon charged (oil or gas). Average porosities of most of these reservoirs were obtained from core analysis, and a few porosity data were taken from well log interpretations. Detrital constituents of the sandstones are mainly quartz, feldspar, and granitic/gneissic rock fragments. Sandstones were grouped into three main reservoir types, based on composition (detrital quartz content) and grain sorting: Type I (average quartz content <50%) are very coarse grained to conglomeratic, poorly to very poorly sorted lithic arkoses. Rock fragments are mainly granitic/gneissic and coarse grained. Type II (average quartz content ranging from 50% to 70%) are fine- to coarse-grained (pebbles absent or occurring in small percentages), moderately sorted arkoses. Type III (average quartz content >80%) are fine to coarse, moderately to poorly sorted quartz arenites or subarkoses. Plots of average porosity against depth show great dispersion in porosity values; such dispersion is mostly due to differences in the reservoir burial histories. However, plotting porosity values against the TDI for individual reservoir types produces well-defined trends. The decrease in porosity is less marked in Type III reservoirs, intermediate in Type II, and faster in Type I. Such plots suggest that it is possible to make relatively accurate porosity predictions based on reservoir TDI, texture, and composition,: within the constraints of reservoir depth/age and basin tectonics analyzed in this study.